Strategi Efektif Organisasi Bimbingan dan Konseling dalam Mendukung Perkembangan Karakter Siswa - Laila Niswah; Abel Yolanda; Iksan Hakiki Pasaribu; Hidayani Syam (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Student character development is one of the important factorsin creating a quality next generation. In this regard, guidanceand counseling organizations have a significant role in implementing effective strategies to support students' character development. By using planned character guidance programs, responsive personal approaches, and integrating character education into the curriculum, these organizations can tailor interventions to the specific needs of each student. In addition, parental participation and collaboration with extracurricular activities provide more comprehensive support in the character learning process. Regular assessment of the implemented program ensures that the strategies used remain appropriate and effective. By creating a positive and motivating school atmosphere, the guidance and counseling organization makes a significant contribution in shaping students who are not only academically intelligent, but also have integrity and good social attitudes. Through this collaboration, it is hoped that students can develop into responsible individuals and have strong characters, ready to face various challenges in the future. The development of student character is one of the important factors in creating a quality next generation. In this case, guidance and counseling organizations have a significant role in implementing effective strategies to support students' character development.